Transculture, Civil Society, or Capitalism? An Interview with Delia Aguilar - Penuela, May (Archīum Ateneo, 2024)
In the interview with Delia Aguilar, she critiques this unwarranted embrace of globalization, where “cheap access to information superhighway” is now possible, “heralding entirely new channels for instantaneous exchanges that would include every remote corner of the world, resulting in the evolution of a ‘transculture’ with its presumably leveling consequences.” Delia Aguilar posits that this view of globalization obscures a true analysis on the dynamics of class and production. Thus, Aguilar urges the vacuousness of academic writing, and to focus attention, instead, on the “dirt and grime of the workaday world.” More importantly, she urges the academics to adjust their framing device, that way they would have the eye and the savvy to expose the “predations of global capitalism and bringing into view what now appears like a wonderful New World Order.”